2022
DOI: 10.53730/ijhs.v6ns1.4757
|View full text |Cite
|
Sign up to set email alerts
|

A review of the effects of lifestyle and nutrition on infertility in couples

Abstract: Infertility is one of the most important life crises that leads to numerous psychological problems and stressful experiences. Investigating the factors affecting infertility is of high significance to help these people in the midwifery profession. One of these important factors is lifestyle. The purpose of present study is to review the studies conducted on the effects of lifestyle on infertility in couples. This systematic review was conducted by searching the keywords including infertility, lifestyle, nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Such a program is likely to result in health promotion, wellbeing, self-actualization, confidence, satisfaction, and better feelings among populations. It seems that paying attention to this type of lifestyle may include general healthy behaviors throughout one's life ( 2 ). In addition, another study showed that health literacy levels were associated with mental, physical, and environmental aspects, yet they were not associated with lifestyle ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such a program is likely to result in health promotion, wellbeing, self-actualization, confidence, satisfaction, and better feelings among populations. It seems that paying attention to this type of lifestyle may include general healthy behaviors throughout one's life ( 2 ). In addition, another study showed that health literacy levels were associated with mental, physical, and environmental aspects, yet they were not associated with lifestyle ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The HELIA Questionnaire was localized by Montazeri, et al ,with its reliability and validity confirmed(the Cronbach's alpha coefficient ranging from 0.72 to 0.89)( 16 ). This questionnaire had two parts, including part “a” on demographic characteristics that contained 6 questions (marital status, sex, age, education level, residence place, and occupation)and part “b” with 33 items in the five fields of accessibility (6 items), reading skills (4 items), comprehension (7 items), evaluation (4 items), and decision making (12 items).The questions were ranked as quite easy ( 5 ), easy ( 4 ), neither easy nor hard ( 3 ), hard ( 2 ), and quite hard ( 1 ). In addition, the maximum and minimum scores of this questionnaire were 165 and 33, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations